1984
DOI: 10.1002/crat.2170190917
|View full text |Cite
|
Sign up to set email alerts
|

The Proton‐induced kossel effect and its application to crystallographic studies

Abstract: A survey is given of the characteristic features of the proton-induced Kossel effect and its use for crystallographic investigations of semiconductor materials. The excitation of t h e characteristic X-rays was performed with protons in the energy range 0.5 -1.5 MeV. Mainly long-wave X-radiation was used because of t h e high X-ray yields and large Bragg angles also for reflections with low indices. The use of the effect for lattice parameter determinations, t h e identification of polar surfaces and the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Comparison of experimental and DFT-calculated values of (a) a and (b) c lattice parameters. Black solid line represents perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of experimental and DFT-calculated values of (a) a and (b) c lattice parameters. Black solid line represents perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
“…As already mentioned in Section 3.2, the diffraction of particle-induced X-rays by the crystal lattice can also be used for material analysis. Geist and Ascheron have demonstrated that the proton-induced Kossel effect can be applied to crystallographic studies [136]. Especially the lattice parameter determination of binary and ternary compounds is described and the influence of proton irradiation and thermal expansion is investigated.…”
Section: Ctystal Effects In Materials Analysismentioning
confidence: 99%